Temperature-controlled friction stir welds of age-hardenable aluminum alloys characterized by positron annihilation lifetime spectroscopy. (May 2023) - Hunt, Johnathon Bryce; Pearl, David; Hovanski, Yuri; Dryzek, Ewa; Dymek, Stanisław; Hamilton, Carter
Friction stir welds were manufactured from aluminum alloy 2024-T3 and 7075-T6 workpieces under temperature control. Three control conditions, high-temperature, low-temperature and uncontrolled, were selected for each alloy based on the precipitation/dissolution temperatures of their strengthening phases, and the welds were characterized through positron annihilation lifetime spectroscopy and mechanical testing. For 2024, positron lifetimes and numerical simulation of the temperature profiles demonstrated that the S phase dissolution temperature was not achieved for any of the control conditions and hardness recovery upon cooling did not occur; however, for the low-temperature control (410°C), the S phase precipitated adjacent to the weld zone with the least extent of overaging, yielding the highest tensile strength of the three conditions. For 7075, dissolution of the η phase did not occur for the low-temperature (390°C) and the high-temperature (430°C) control conditions, and the low-temperature control produced the highest tensile strength due to the lesser degree of overaging of the strengthening phase. The uncontrolled condition for 7075, however, did achieve temperatures capable of dissolving the η phase, but due to the slow natural aging kinetics of 7075, a hardness recovery was not observed within the timeframe of this investigation.